2014
DOI: 10.1177/1754073914544476
|View full text |Cite
|
Sign up to set email alerts
|

There’s No Crying in Baseball, or Is There? Male Athletes, Tears, and Masculinity in North America

Abstract: We explore men’s negotiation of emotional expression within larger social discourses around masculinity. Drawing on the phenomenon of men’s crying within the competitive sports context, we demonstrate that although the prevailing image of men’s emotion is one of constricted expression and experience, inexpressivity is representative neither of typical nor ideal masculinity in contemporary dominant culture. We first review the literature on prevailing cultural beliefs about normative male emotional expression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 37 publications
1
48
0
Order By: Relevance
“…Overall, findings of Study 2 are consistent with research cited previously showing that male athletes in stereotypically masculine sports seem to have increased freedom to display emotions that might be seen as "unmasculine" in other settings (Wong et al, 2011;MacArthur and Shields, 2015). No research to my knowledge has investigated expressions of emotion, or attitudes toward it, in sports considered less stereotypically masculine (e.g., swimming, figure skating, badminton).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Overall, findings of Study 2 are consistent with research cited previously showing that male athletes in stereotypically masculine sports seem to have increased freedom to display emotions that might be seen as "unmasculine" in other settings (Wong et al, 2011;MacArthur and Shields, 2015). No research to my knowledge has investigated expressions of emotion, or attitudes toward it, in sports considered less stereotypically masculine (e.g., swimming, figure skating, badminton).…”
Section: Discussionsupporting
confidence: 86%
“…In addition, Study 2 revealed that men may be aware of the advantages of crying in a stereotypially masculine setting, in reporting that they would be more likely to cry in a stereotypically masculine versus feminine setting; no difference emerged for female targets. Overall, the results shed light on why men's crying may be particularly prominent in settings that are perceived to be highly masculine, such as men's competitive sports (MacArthur and Shields, 2015). Results also highlight that beliefs about emotion are fundamentally tied to beliefs about gender, both in our perceptions of others' displays of emotion and in judgments about our own.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Much of the work on crying has dealt with gender issues, with crying by males seen as more inappropriate than crying by females, especially in the eyes of other males (Cretser et al, 1982). Studies in sports contexts have found that male players who display low-intensity, moderate crying (e.g., "tearing up") are perceived as having higher self-esteem compared with players who cry more intensely (Wong et al, 2011;MacArthur and Shields, 2014). Warner and Shields (2009b) examined how the intensity of tears (as opposed to merely their presence or absence) affected evaluations of men and women.…”
Section: Intensitymentioning
confidence: 99%
“…However, both an extravagantly expressive and a restrained emotional ex-pressive style are expected of both genders to some degree and depending on the context. Thus, MacArthur and Shields (2015) underlined that passionate restraint represents a relevant norm for women as well, especially in contexts that demand "good judgment. "…”
mentioning
confidence: 99%